Human heart modeling / Azrizal Ismail - Azrizal, Ismail (2003)
Medical imaging technology plays an important role in providing efficient, reliable medical services. In today’s technology, most imaging modalities provide individual 2D images for study. However, when internal visualization is necessary, 2D images will not provide medical professionals with complete and precise data, which is important in planning surgeries. If 3D volume images of the anatomy being studied can be viewed, the user will be able to get acurate view and understanding of the problem. This project intends to construct a human heart modeling for the purpose of volume visualization. The volumetric data will be first obtained through a series of data conversions and read into the system. Next, it will be first be projected in a 3D view. The system will allow the user to select a cutting image and interactively slice the volume image, where the user chooses. This will allow internal visualization of the volume. This system will contribute in aiding medical professionals in simulation and planning of disscult surgeries, and can be used for educational purposes as well.